A randomized algorithm for finding a path subject to multiple QoS constraints - Korkmaz, T.; Krunz, M. (Global Telecommunications Conference (GLOBECOM), 1999 IEEE, 1999)
An important aspect of quality-of-service (QoS) provisioning in integrated networks is the ability to find a feasible route that satisfies end-to-end QoS requirements of a connection request while efficiently using network resources. In general, finding a path subject to multiple additive constraints (e.g., delay, delay-jitter) is an NP-complete problem. For this problem, we propose a randomized heuristic algorithm with polynomial-time complexity. Our algorithm first prunes all the links that cannot be on any feasible paths. It then uses a randomized heuristic search to find a feasible path, if one exists. The worst-case computational complexity of our algorithm is O(n/sup 2/), where n is the number of nodes. The storage complexity of the algorithm is O(n). Using extensive simulations, we show that our algorithm gives very high success rate in finding feasible paths.